STRATEGI PEMANFAATAN TEKNOLOGI KOMPUTER UNTUK ASESMEN HYBRID KEMAMPUAN MEMBACA SISWA SEKOLAH DASAR DI DAERAH TERPENCIL - Beng, Jap Tji; Arisandi, Desi; Arumsari, Chysanti; Tiatri, Sri (Jurnal Bakti Masyarakat Indonesia, 2019)
The use of computer technology has become an inseparable part of every learning activity, including its use as an assessment aid in the field of education. Reading Bahasa Indonesia is a basic skill that needs to be mastered by elementary school students, but in reality the development of the reading skill of each student is not the same. Reading assessment is needed primarily to identify reading difficulties as early as possible, so that appropriate interventions can be made, which enable a student to follow the knowledge development of their peer group. At the beginning of this study, the reading skill assessment material developed was paper and pencil based. Calibration of measuring instruments used in the assessment is carried out continuously and carefully. In the next stage, to facilitate the assessment process, three prototypes of computer technology application -based assessment were developed: (a) online server-based assessment, (b) stand-alone computer-based assessment, and (c) hybrid assessment with interactive scoring using paper and pencil. All three types of prototypes are tested and evaluated in different conditions and environments. The trial results show that the prototype hybrid assessment is most suitable for use in elementary schools in remote locations. This hybrid assessment has been implemented in three remote elementary schools: one in Karanganyar, and two in Salatiga. All three elementary schools have minimal internet networks, and limited teacher and student computer literacy. The results of the application in the three remote locations show that for the assessment of remote area elementary school students, using hybrid computer technology is the most appropriate. Other findings indicate that the application of hybrid assessment is a faster, easier, and more economical method, compared to the paper and pencil method ABSTRAK: Pemanfaatan teknologi komputer sudah menjadi bagian yang tidak terpisahkan dari setiap kegiatan pembelajaran, termasuk penggunaannya sebagai alat bantu asesmen di bidang pendidikan. Membaca dalam Bahasa Indonesia merupakan kemampuan dasar yang perlu dikuasai siswa Sekolah Dasar, namun kenyatannya perkembangan kemampuan membaca tiap siswa tidak sama. Asesmen membaca diperlukan terutama untuk mengidentifikasi kesulitan membaca sedini mungkin, agar dapat dilakukan intervensi yang tepat, yang memungkinkan seorang siswa mampu mengikuti perkembangan pengetahuan untuk kelompok sebayanya. Pada awal penelitian ini, materi asesmen kemampuan membaca yang dikembangkan adalah berbasis kertas dan pensil. Kalibrasi alat-alat ukur yang digunakan dalam asesmen dilakukan secara berkelanjutan dan hati-hati. Pada tahap selanjutnya, guna mempermudah proses asesmen, tiga prototype asesmen berbasis aplikasi teknologi komputer dikembangkan: (a) asesmen berbasis online server, (b) asesmen berbasis komputer stand-alone, dan (c) asesmen hybrid dengan skoring interaktif menggunakan kertas dan pensil. Ketiga jenis prototype diuji dan dievaluasi dalam kondisi dan lingkungan yang berbeda-beda. Hasil ujicoba menunjukkan prototype asesmen hybrid paling sesuai diterapkan di Sekolah Dasar di lokasi terpencil. Asesmen hybrid ini telah diterapkan di tiga Sekolah Dasar daerah terpencil: satu di Karanganyar, dan dua di Salatiga. Ketiga Sekolah Dasar tersebut memiliki jaringan internet yang minim, dan literasi komputer guru dan siswa yang terbatas. Hasil penerapan di tiga lokasi terpencil itu menunjukkan bahwa untuk asesmen siswa Sekolah Dasar daerah terpencil, yang paling sesuai adalah pemanfaatan teknologi komputer secara hybrid. Temuan lain menunjukkan bahwa penerapan asesmen hybrid merupakan metode yang lebih cepat, lebih mudah, dan lebih ekonomis, dibandingkan dengan metode kertas dan pensil.